Perbedaan Perubahan Tekanan Darah Arteri Rerata antara Penggunaan Diazepam dan Midazolam sebagai Premedikasi Anestesi - Donda, Melissa; Sudjito, Hadi; Wicaksono, Bagus (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2014)
Background: Diazepam and midazolam is used as premedication for anesthesia. Diazepam and midazolam as the benzodiazepine drugs can cause changes in mean arterial pressure. This study aimed to prove the difference in mean arterial pressure changes between diazepam and midazolam as premedication for general anesthesia. Methods: This was an observational analytic study with cross-sectional method. Using consecutive sampling, we selected patients who fulfill the inclusive and exclusive criterias. Thirty patients were selected and divided into group of diazepam and midazolam. The first group was given diazepam 0.07 mg/kg intravenously and the second group was given midazolam 0.07 mg/kg intravenously. The blood pressure is recorded before giving the premedication and in five minutes after giving the premedication. The differences in mean arterial blood pressure between the two groups were analyzed by independent t-test. Results: The result showed a non-significant difference in mean arterial pressure before the administration (p=0.198, p>0.05) and five minutes after the administration of diazepam and midazolam (p=0.335, p>0.05). Conclusions: There is no significant difference in mean arterial pressure when using premedication of Diazepam and Midazolam administration. Keywords: Diazepam, Midazolam, Mean Arterial PressureÂ